EVALUATING THE EFFECTIVENESS OF THE MODELS FOR ASSESSING THE INITIATION OF BANKRUPTCY PROCEEDINGS - Milić, Dragan; Jocic, Bogdan; Novaković, Dragana; Zekić, Vladislav; Novaković, Tihomir; Radišić, Maja; Radišić, Mladen (Economics of Agriculture, 2025)
Using predictive models for assessing the initiation of bankruptcy proceedings constitutes a proactive strategy aimed at preserving financial stability and promoting the long-term viability of businesses. This study focuses on companies in the agricultural and food production sectors within the Republic of Serbia, specifically examining those for which bankruptcy proceedings were initiated in 2022, based on their operational activities in 2021. The primary objective of this research is to evaluate the efficiency of the predictive models in forecasting the likelihood of bankruptcy proceedings one year before their initiation. The requisite data for applying these models were obtained from the financial statements of the analyzed companies. The findings indicate that the Vlaović Begović (VB) model demonstrated the highest efficacy in predicting the onset of bankruptcy proceedings within the agricultural sector. Conversely, the Altman Z’ score proved to be the most appropriate model for assessing bankruptcy within the food sector.